Forging parliamentary space: revolutionary assemblies in New Granada and Spain, 1810–31. (4th May 2017) - Luengo, Jorge
SUMMARY: This article analyses the making of space in modern parliamentarism from a transatlantic perspective. By considering the case studies of New Granada and Spain between 1810 and 1831, this article focuses on the differences in shaping parliamentary space during the revolutionary period in Europe and the Americas. This study considers the multiplicity of spaces in the construction of parliaments as modern institutions. It also discusses the influences of early modern estate parliaments in the construction of new institutional space in revolutionary times. In the process, several elements will be considered, such as the choice of the town where parliaments convene and the internal organization of the assembly hall. It is argued that, despite similar issues beyond the construction of a new institution, the influence of the king's presence in Spain led to a different shape of internal parliamentary space compared to New Granada. Such an approach makes an original contribution to the debates on the transformation of sovereignty during this period and it therefore reshapes the interpretation of the revolutionary process from a cultural perspective.